Effect Of Compensation And Carerr Development To The Employee Performance (Study At PT. Benesse Indonesia) - Yayan Sudaryana (Journal of Management Review, 2020)
The gap in services often occurs between the provider and costumers. The purpose of this study is to perceive and prove empirically the influence of compensation and career development to the performance in PT. Bennese Indonesia. This research using a quantitative approach with a quotation of the sample is 107 employees. The data analysis techniques using statistical descriptive analysis, validity and reliability testing, multiple regression analysis, hypothesis testing through the coefficient of determination test, simultaneous test, and the significance of individual parameters. These results of this research indicate that (1) each compensation and career development has a positive effect on employee performance; as well as (2) compensation and career development have a significant effect on employee performance simultaneously.